Food allergomics based on high-throughput and bioinformatics technologies. (April 2020) - Wang, Chong; Wang, Yanbo; Liu, Guangming; Fu, Linglin
Graphical abstract: Highlights: Food allergy is a serious food safety problem with limited controlling methods. Allergomics is the discipline to study the repertoire of allergens. Allergomics can facilitate the controlling of food allergy. Four common allergomics strategies are reviewed in detail. Allergomics is a powerful approach but requires far more development. Abstract: Food allergy is a serious food safety problem worldwide, and the investigation of food allergens is the foundation of preventing and treating them, but relevant knowledge is far from sufficient. With the advent of the "big data era", it has been possible to investigate food allergens by high-throughput methods, proposing the concept of allergomics. Allergomics is the discipline studying the repertoire of allergens, which has relatively higher throughput and is faster and more sensitive than conventional methods. This review introduces the basis of allergomics and summarizes its major strategies and applications. Particularly, strategies based on immunoblotting, phage display, allergen microarray, and bioinformatics are reviewed in detail, and the advantages and limitations of each strategy are discussed. Finally, further development of allergomics is predicted. This provides basic theories and recent advances in food allergomics research, which could be insightful for both food allergy research and practical applications.